Randomized controlled trial protocol to analyze the effects of rice with different contents of resistant starch on chronic constipation - Yiping Zhao; Fanyu Zhao; Qian Liu; Li Liu; Fang Wang; Xiuying Hu (Scientific Reports)
Abstract The trend of the aging population worldwide is becoming increasingly severe. As people age, constipation becomes increasingly common in older adults, causing varying degrees of physical and psychological harm to them. Dietary intervention is a common nonpharmacological therapy. Resistant starch is a type of dietary fiber that can regulate the gut microbiota and alleviate chronic constipation. However, few studies have explored the effects of different types of rice on chronic constipation in older adults. This protocol aims to evaluate the effects of rice with different contents of resistant starch on chronic constipation in old adults. This trial is a double-blind, two-arm randomized controlled trial. Older adults with chronic constipation residing in long-term care facilities will be recruited. Participants will be randomly assigned to receive A rice (resistant starch: 11-20%) or receive B rice (resistant starch: 0.1-0.5%). Both groups will adopt the serving of individual dishes, and the nutrition experts calculated the consumption of rice in the two groups according to the different conditions of each older person to ensure that the number of calories in the meal remained unchanged and that the other dietary components remained unchanged. The intervention will last for a total of 24 weeks. Participants will undergo follow-up via questionnaires at 6, 12, and 24 weeks during the intervention. The primary outcome will be constipation symptoms assessed by the Wexner questionnaire. The secondary outcomes will be quality of life, depression, anxiety and sleep quality. This is the first randomized controlled trial on the effects of rice with different contents of resistant starch on chronic constipation in older adults. It is expected that this study, if proven effective in relieving constipation symptoms in older adults, will provide evidence-based constipation care for medical staff. Trial registration number: retrospectively registered on Chinese Clinical Trial Registry.